Sifat Dan Morfologi Wood Plastic Composite Berbasis Batang Sawit Dengan Kadar Lignoselulosa yang Berbeda - Melly Anggraeni; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Plantations of the palm in Indonesia is very large included Riau Province. It cause the palm trunk be the most waste and it has the potential to be utilized for manufacturing Wood Plastic Composite (WPC). Properties of the palm trunk is different and it has many weakness. Knowledge of stem’s lignocellulose can be easier to modify suitable materials for compatibility between WPC components. The main objective of this study is to determine the percentage of palm trunk parts longitudinally, to determine the lignocellulose component before and after preparation using oxalic acid, to evaluate the effect of palm trunk parts longitudinally and ratio of wood flour/polypropylene to the properties and morphology of WPC. The composition of wood flour was 100 mesh as filler and polypropylene as matrix are 50/50; 60/40; 70/30 with mixture of 2% paraffin as plasticizer, 5% maleic anhydride (MAH) and 5% Benzoyl peroxide (BPO). The palm trunk was prepared using oxalic acid at 120oC for 15 minutes. WPC samples were prepared using internal mixer Labo Plastomill at temperature 170oC and rotor speed 80 rpm. Testing experiments were prepared to mechanical properties consists of tensile strength and elastic modulus (MOE) and physical properties consists density, water absorption and swelling thickness. Scanning Electron Microscopy was used as a morphology testing with 50x and 500x magnification. The results showed that each part of palm and ratio of wood flour/polypropylene gives an influence. The best of WPC material is the base of stem at 70/30 ratio with tensile strength 15,125 MPa, MOE 2.308, 303 MPa, density 0,854 gr/cm3, water absorption 0,565%, and swelling thickness 0,133%.Keywords: lignocellulose, palm trunk, wood plastic composite